Myths versus Truths regarding the Novel Coronavirus Disease (COVID-2019) Outbreak - Amgain, Kapil; Neupane, Sujana; Panthi, Laxmi; Thapaliya, Pooja (Journal of Karnali Academy of Health Sciences, 2020)
Background: The Corona Virus Disease (COVID-19) is a novel infectious disease caused by the COVID-19 Virus. This virus belongs to the family of SARS (Severe Acute Respiratory Syndrome) and classified as SARS-CoV-2, a positive-sense single-stranded RNA virus that is causing an ongoing global pandemic. The outbreak of this novel Coronavirus (nCoV-19) is causing great fear in public due to its rapid spread over 200 countries worldwide and created a global Public Health Emergency. The virus is an intracellular obligatory parasite that can even infect bacteria called Bacteriophage. Unlike Bacteria, Virus is not a living microorganism and can’t multiply in the outer environment. If we draw a line in between the living and non-living, it lies in the border3. However, the peculiar characteristic of the virus is that it can be living after entering the body of the living organism, causing harmful effects. Since it behaves like dust or dirt outside of our body, it is better to wash them out and prevent it to enter our bodies. In this way, the best way of prevention of this novel COVID-19 viral disease is to wash it out from our hand, rather than killing it by using a disinfectant, hand sanitizer, alcohol-based rub, etc. Key Message: Don’t Get the Virus, Don’t Give the Virus. Since COVID-19 Virus can enter the body from the reservoir mainly through respiratory droplets during coughing, keeping social distance and proper hand-washing are the best way to preventive measure. To prevent the rapid spreading of COVID-19, please strictly follow the following five precautionary and preventive measures yourself and ask others too. HANDS – wash them often with soap and water ELBOW – cough into it FACE – don’t touch it SPACE – keep social distance (> 3feets) FEEL SICK? - Stay home (with proper nursing care)